Palm Juice / Nira (Arenga pinnata (Wurmb) Merr.), A Source of Lactic Acid Bacteria from North Sumatra - It Jamilah; Nunuk Priyani; Maretta Fitriani Silaban (Talenta Conference Series: Science and Technology (ST), 2018)
Palm juice or so called Nira in North Sumatera, is a liquid produced from the base of the male flower bunches from sugar palm or Aren (Arenga pinnata L.). Nira contain sugar and other nutritional components that are suitable for the growth of microorganisms; one of which lactic acid bacteria (LAB). The purpose of this study was to isolate LABs that could inhibit growth of food pathogenic bacteria and to evaluate their potencies as probiotic candidates. Evaluation on probiotic properties were obtained from: - Antagonisms assay against representative food pathogens (Salmonella typhimurium, Staphylococcus aureus and Escherichia coli), - Survivability within simulated gastrointestinal tract (Gastric pH (2.0), - Intestinal pH (7.2), - Bile salts (0.5% oxgall), and - ability to form biofilm on the surface of solid stainless steel. Sixteen LABs were isolated and only six isolates had showed antagonisms against food pathogens. Five LABs namely MF5, MF10, MF11, MF14 and MF15 were able to survive in simulated condition of gastrointestinal tract and to form biofilm on the surface of solid stainless steel. The results showed prospective aspects of LABs as local probiotic candidates.